Effects of trade liberalisation on the environment in the manufacturing sector. - BEGHIN, John (1997)
Analyses environment-growth-trade linkages and the implications of international specialisation in industrial production at different development levels. Considers the impact of globalisation on trade flows and resulting potential environmental problems.